Pengaruh Variasi Komposisi Serat Daun Nanas Terhadap Kekuatan Impact Komposit Hybrid Berlapis Serat Karbon Spakbor Sepeda Motor - Amelia Putri (CV. SINAR HOWUHOWU, 2026)
This study analyzes the effect of varying pineapple leaf fiber (PALF) compositions on the impact strength of carbon fiber-reinforced hybrid composites intended for motorcycle fender applications. The composites were fabricated using the hand lay-up method with an epoxy resin matrix and a carbon–PALF–carbon stacking sequence. PALF compositions of 30%, 50%, and 70% of the total reinforcement fraction were utilized, maintaining a resin-to-fiber ratio of 60:40. Impact testing was conducted using the Charpy method in accordance with ASTM D6110. The results indicate that PALF composition influences the composite's impact strength. The 30% PALF composition yielded the highest values, with an average impact energy of 21.331 J and an impact strength of 0.400 J/mm², followed by the 50% PALF composition (19.782 J and 0.308 J/mm²) and the 70% PALF composition (18.133 J and 0.252 J/mm²). The decrease in impact strength at higher PALF compositions is attributed to uneven fiber wetting by the resin, which weakened the fiber-matrix bond and promoted cracking, delamination, and fiber pull-out. Consequently, the composite with 30% PALF demonstrated the best impact performance. However, further research involving improved control of the fabrication process is required to obtain more accurate and representative results.